2020
DOI: 10.1007/s12098-020-03194-2
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Regression Equations for Forced Oscillation Technique – A Much Needed Affair

Abstract: Measurement of lung function is an essential component for making decision in patients with obstructive lung diseases. Spirometry is considered as the gold standard for assessment of lung function, both for diagnosis and monitoring in patients with asthma. However, it is difficult to be performed by smaller children due to its effort dependent nature and need for cooperation. Forced Oscillation technique (FOT) is a novel and effort independent pulmonary function test for diagnosis of airway obstruction requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although several studies have reported the reference values of FOT data, 6 it was also reported that the normal values of resistance (Rrs) and reactance (Xrs) differ depending on ethnicity, sex, standing height, age, body weight, oscillometric devices, and measuring techniques. 7 In Japan, reference values for FOT measurements in middle-aged and elderly Japanese individuals have been published. 8 However, 44.8% of the population included in that study had abnormal spirometric findings, and it is unclear how many subjects had abnormal chest radiography findings.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported the reference values of FOT data, 6 it was also reported that the normal values of resistance (Rrs) and reactance (Xrs) differ depending on ethnicity, sex, standing height, age, body weight, oscillometric devices, and measuring techniques. 7 In Japan, reference values for FOT measurements in middle-aged and elderly Japanese individuals have been published. 8 However, 44.8% of the population included in that study had abnormal spirometric findings, and it is unclear how many subjects had abnormal chest radiography findings.…”
Section: Introductionmentioning
confidence: 99%